Confronting Globalization: The Challenges of Creating Space for Global Learning - Staffan Larsson; Madeleine Abrandt Dahlgren; Shirley Walters (Adult Education Research Conference, 2002)
This study describes and analyses the challenges encountered in a recent case of global collaboration in developing a web-based masters program for adult educators. “Agency,” “structure,” and “frame factor” are used as analytical concepts to help understand the dynamics of the collaboration and the character of the program produced.